Cruzipain Sulfotopes-Specific Antibodies Generate Cardiac Tissue Abnormalities and Favor Trypanosoma cruzi Infection in the BALB/c Mice Model of Experimental Chagas Disease - Soprano, Luciana L.; Ferrero, Maximiliano R.; Landoni, Malena; García, Gabriela A.; Esteva, Mónica I.; Couto, Alicia S.; Duschak, Vilma G. (Frontiers in Cellular and Infection Microbiology, 2022)
Trypanosoma cruzi Cruzipain (Cz) bears a C-terminal domain (C-T) that contains sulfated epitopes “sulfotopes” (GlcNAc6S) on its unique N-glycosylation site. The effects of in vivo exposure to GlcNAc6S on heart tissue ultrastructure, immune responses, and along the outcome of infection by T. cruzi, were evaluated in a murine experimental model, BALB/c, using three independent strategies. First, mice were pre-exposed to C-T by immunization. C-T immunized mice (C-TIM) showed IgG2a/IgG1 < 1, induced the production of cytokines from Th2, Th17, and Th1 profiles respect to those of dC-TIM, which only induced IL-10 respect to the control mice. Surprisingly, after sub-lethal-challenge, both C-TIM, and dC-TIM, showed significantly higher parasitaemia and mortality than control group. Second, mice exposed to BSA-GlcNAc6S as immunogen (BSA-GlcNAc6SIM) showed: severe ultrastructural cardiac alterations while BSA-GlcNAcIM conserved the regular tissue architecture with slight myofibrils changes; a strong highly specific humoral-immune-response reproducing the IgG-isotypes-profile obtained with C-TIM; and a significant memory-T-cells-response demonstrating sulfotope-immunodominance respect to BSA-GlcNAcIM. After sub-lethal challenge, BSA-GlcNAc6SIM showed exacerbated parasitaemias, despite elevated IFN-γ levels were registered. In both cases, the abrogation of ultrastructural alterations when using desulfated immunogens supported the direct involvement of sulfotopes and/or indirect effect through their specific antibodies, in the induction of tissue damage. Finally, a third strategy using a passive transference of sulfotopes-specific antibodies (IgGs-GlcNAc6S) showed the detrimental activity of IgGs-GlcNAc6S on mice cardiac tissue; and mice treated with IgGs-GlcNAc6S after a sub-lethal dose of T. cruzi, surprisingly reached higher parasitaemias than control groups. These findings confirmed the indirect role of the sulfotopes, via their IgGs-GlcNAc6S, both in the immunopathogenicity as well as favoring T. cruzi infection.